Trends in prescribing patterns of antiepileptic drugs among older adult inpatients in a Brazilian tertiary center - Telma ASSIS; Aroldo BACELLAR; Luan CÔRTES; Silas SANTANA; Gersonita COSTA; Osvaldo NASCIMENTO (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Data on prescribing patterns of antiepileptic drugs (AEDs) to older adult inpatients are limited. Objective: To assess changes in prescribing patterns of AEDs to older adult inpatients with late-onset epilepsy between 2009-2010 and 2015-2019, and to interpret any unexpected patterns over the 2015-2019 period. Methods: Patients aged ≥60 years with late-onset epilepsy from a tertiary center were selected. Demographic data, seizure characteristics and etiology, comorbidities, and comedications were analyzed, in addition to prescription regimens of inpatients taking AEDs to treat epilepsy. AED regimens were categorized into two groups: group 1 included appropriate AEDs (carbamazepine, oxcarbazepine, valproic acid, gabapentin, clobazam, lamotrigine, levetiracetam, topiramate, and lacosamide); and group 2 comprised suboptimal AEDs (phenytoin and phenobarbital). Multivariate logistic regression analysis was performed to identify risk factors for prescription of suboptimal AEDs. Results: 134 patients were included in the study (mean age: 77.2±9.6 years). A significant reduction in the prescription of suboptimal AEDs (from 73.3 to 51.5%; p<0.001) was found; however, phenytoin remained the most commonly prescribed AED to older adult inpatients. We also found an increase in the prescription of lamotrigine (from 5.5 to 33.6%) and levetiracetam (from 0 to 29.1%) over time. Convulsive status epilepticus (SE) and acute symptomatic seizures associated with remote and progressive etiologies were risk factors for the prescription of suboptimal AEDs. Conclusions: Phenytoin was the main suboptimal AED prescribed in our population, and convulsive SE and acute symptomatic seizures associated with some etiologies were independent risk factors for phenytoin prescription. These results suggest ongoing commitment to reducing the prescription of suboptimal AEDs, particularly phenytoin in Brazilian emergence rooms.